What Factors Are Associated With Recent Changes in Men’s Attitudes Towards Intimate Partner Violence Across Regional, Rural, and Urban Spaces of Ghana? Findings From Three Waves of Ghana National Surveys From 2003 to 2014 - OLA, Bamidele Emmanuel (Journal of interpersonal violence, 2022)
Numerous studies have shown that men?s attitudes towards intimate partner violence (IPV) remain a strong predictor of its actual perpetration. Very few trend studies available have also reported that IPV-acceptance is gradually declining globally. However, almost none of these trend studies have included men in their samples, nor have investigated factors associated with changes in men?s attitudes towards IPV. To supplement this sparse knowledge, the current study employed three waves of the Ghana Demographic and Health Survey (GDHS): 2003 (n=4,901), 2008 (n = 4,481), and 2014 (n = 4,333) data, and reports trends and patterns in men?s attitudes towards wife-beating at national, regional, and rural-urban residences of Ghana. Multivariable logistic regression models were fitted to further examine the key socioeconomic and cultural factors significantly associated with men?s acceptance of IPV at 95% confidence interval. The results show that men?s acceptance of wife-beating declined largely at the national level by 60.8% between 2003 and 2014: from 31.7% in 2003 to 12.4% in 2014. However, when disaggregated by region, data revealed a slight increase in men?s IPV-acceptance in two regions between 2008 and 2014?the Western and Upper East regions, by 2.1% and 3.8%, respectively. Having less than secondary education, being in a polygynous union, and residence in certain regions, was significantly associated with justification of wife-beating. Whereas having access to media was not consistently significant in influencing men?s attitudes against wife-beating, especially in the rural areas. The decreasing significance of education, household wealth, and religion in the 2014 wave (especially in urban areas) seem to suggest that recent decline in men?s acceptance of wife-beating may not have been driven by a single isolated factor, but by complex interactions of several exogenous factors including those not captured in the current data. Study implications and need for further studies are discussed.